2021
DOI: 10.3390/ijgi10040251
|View full text |Cite
|
Sign up to set email alerts
|

Mapping Public Urban Green Spaces Based on OpenStreetMap and Sentinel-2 Imagery Using Belief Functions

Abstract: Public urban green spaces are important for the urban quality of life. Still, comprehensive open data sets on urban green spaces are not available for most cities. As open and globally available data sets, the potential of Sentinel-2 satellite imagery and OpenStreetMap (OSM) data for urban green space mapping is high but limited due to their respective uncertainties. Sentinel-2 imagery cannot distinguish public from private green spaces and its spatial resolution of 10 m fails to capture fine-grained urban str… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

0
25
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 47 publications
(25 citation statements)
references
References 76 publications
0
25
0
Order By: Relevance
“…For instance, Taylor et al [50] used Google Earth to measure the quality of urban green spaces. Similarly, Ludwig et al [49] showed that combining OSM data with Sentinel-2 satellite imagery improves assessment of urban green spaces.…”
Section: Discussionmentioning
confidence: 98%
See 1 more Smart Citation
“…For instance, Taylor et al [50] used Google Earth to measure the quality of urban green spaces. Similarly, Ludwig et al [49] showed that combining OSM data with Sentinel-2 satellite imagery improves assessment of urban green spaces.…”
Section: Discussionmentioning
confidence: 98%
“…Their study shows that the degree of completeness and the quantity of contributions for urban green spaces vary between cities, with a tendency of greater data completeness in city centres and lower data completeness on the city outskirts. A more recent study by Ludwig et al [49] summarizes the challenges encountered by researchers of urban green spaces such as the lack of consensus on the definition of "urban green space", the unequal sensitivity of data on private and small green spaces, and the differences in land cover indicators between municipal, national, and other geographic information systems datasets.…”
Section: Discussionmentioning
confidence: 99%
“…Given the definition of SDSS (Malczewski, 1999), urban green spaces can be assessed with an SDSS approach in terms of their suitability for several activities by taking user preferences into account. As users expect a change in the results upon their personal preferences, the OAT sensitivity analysis method as a followup step investigates how sensitive the outcome is to different user preferences, which are the criteria weights.…”
Section: Methodsmentioning
confidence: 99%
“…Spatial decision support systems (SDSS) with their various approaches offer the possibility to evaluate the alternatives based on computed characteristics (Keenan and Jankowski, 2019) by integrating spatial data processing and multi-criteria decision making (MCDM) into a computer-based system. They are designed to enable people to make more efficient choices, especially when dealing with spatial decision-making issues (Malczewski, 1999). As, for example in the present case, to choose urban green spaces according to a range of weighted criteria under certain activities.…”
Section: Introductionmentioning
confidence: 99%
“…In contrast, the development of urban GS datasets does not have sufficient resolution and completeness, due to varied definitions of green space and different monitoring methods [30]. The pan-European CORINE Land Cover data set contains a designated class "Green Urban Areas," including GS larger than 25 ha [31].The Urban Atlas [32] for the EU and the Trust for Public Land's ParkServe data set [33] for the US contains land-use information only for selected cities.…”
Section: Introductionmentioning
confidence: 99%